Harmonization of Fetal Life and Women Right to Bodily Autonomy in Pro-Life and Pro-Choice Perspectives - Melisa Manik Septiani; Wahyudi Wahyudi (Journal of Progressive Law and Legal Studies, 2026)
This study examines the legal dilemma in regulating abortion in Indonesia through the conflict between pro-life and pro-choice doctrines. The problem arises from the tension between protecting the right to life of the fetus and the right to bodily autonomy of women within the framework of national health and criminal law. This study aims to analyze how the latest regulations, particularly Law No. 17 of 2023 on Health and the new Criminal Code, seek to harmonize these two interests. The method used is normative legal research with a legislative approach and a conceptual approach through the study of regulations and legal literature. The results of the study show that Indonesian law is still oriented towards a pro-life approach through a general ban on abortion, but provides limited exceptions in cases of sexual violence and medical emergencies. This selective recognition gives rise to normative inconsistencies and double standards in the protection of women's bodily autonomy. This study concludes that existing policies are still partial compromises and recommends a more proportional and reproductive health-based legal approach.